Preparation, characterization of Si doped TiO2 nanotubes and its application in photocatalytic oxidation of VOCs - Zou, X.; Li, Xin Yong; Qu, Z.; Wang, J. (2011)
The Si-doped TiO2 nanotubes photocatalysts was synthesized by anodic oxidation method, which used Na2SiF6/HF as an electrolyte, and was characterized by means of SEM, XRD, DRS and EDX. TiO2 nanotubes composed of anatase phase and rutile phase, and Si was highly dispersed on the wall of TiO2 nanotubes. The photocatalytic activity of the Si-doped TiO2 nanotubes was investigated for photocatalytic degradation of gaseous toluene. It was found that the photocatalytic activity of Si-doped TiO2 nanotubes, which prepared by 0.03 mol · L-1 Na2SiF6/HF and calcined at 400°C for 1 h, was the highest. The conversion of toluene was 60% over the prepared Si doped TiO2 nanotubes under UV light, which was one times higher than that of pure TiO2 nanotubes.